Mixed Economy and its Efficiency - Vengrys, Aleksandras (Ekonomika, 1995)
The modem economy of developed countries can be defined as a mixed economy i.e. a certain stage of a market economy. It is characterized by: 1) mixed type of regulation (a combination of market forces and programming); 2) mixed socioeconomic basis (combination of diverse forms and character of ownership). The Theory of economics investigates the mixed economy in various aspects and levels. The political economy focuses on the macroeconomic analysis of socio-economic basis in a mixed economy; and the economics-on the macroeconomic analysis of efficiency and ways of regulation. Economics reveals that the lower level of pure economic efficiency in a mixed economy (in comparison with the model of perfect competition) could be overly compensated by its social and ecological efficiency.